Development assistance efforts and policies of the members of the Development Assistance Committee : 1964 review - Thorp, Willard L.; Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development (OECD), 1964)
This review examine financial assistance to the less-developed countries under the Organisation for Economic Co-operation and Development.
asm 23/01/2019
Loans
Keywords: Economic assistance; Technical assistance; Developing countries